A novel ammonium zinc molybdate layered double hydroxide nanoflakes/vapor grown carbon fibers nanomaterials based electrocatalyst for the monitoring of dimetridazole drug in real samples. Issue 5 (October 2022) - Karuppiah, Chelladurai; Babulal, Sivakumar Musuvadhi; Chen, Tse-Wei; Chen, Shen-Ming; Hsu, Li-Fan; Al Farraj, Dunia A.; Ramaraj, Sayee Kannan; Elshikh, Mohamed S.; Yang, Chun-Chen
Abstract: Antibiotics are mainly used to treat infectious diseases caused by bacteria in human and animal bodies. Dimetridazole (DMZ) is a nitroimidazole class of antibiotic drug which is commonly used as an additive in poultry feed. The overuse of antibiotics in poultry production can transfer resistant bacteria to living organisms that cause serious side effects. Therefore, we have developed a two-dimensional (2D)/one-dimensional (1D) hybrid electrocatalyst to detect DMZ protozoan infections drug in food samples. A 2D nanoflakes-like structure of hydrogen ammonium zinc molybdate layered double hydroxides (denoted as AZnMo-LDHs), is a new class of 2D material, that was initially derived through the co-precipitation method; later, it was integrated with 1D vapor grown carbon fiber (VGCF) under ultrasonication method. This hybrid material is further characterized by different spectroscopic and microscopic techniques. Its electrocatalytic activity to DMZ was also examined by cyclic and differential pulse voltammetry methods. The AZnMo-LDHs@VGCF electrocatalyst exhibited an excellent electrochemical detection parameter such as a lower limit of detection (0.021 µM), sensitivity (1 µA µM −1 cm −2 ), and good linear range (0.25–570 µM) toward DMZ. It is due to the synergistic effect between the 2D nanoflakes of the LDHs and 1D VGCF conductive support. The proposed sensor further exhibited a good recovery to the determination of DMZ in real spiked samples such as egg, milk, and human urine. Graphical Abstract: ga1 Highlights: Novel hydrogen ammonium zinc molybdate layered double hydroxides (AZnMo-LDHs) was demonstrated. Stable 2D nanoflakes-like morphology derived by co-precipitation and calcination-free approach. 2D/1D (VGCF) hybrid nanostructure was obtained by the sonochemical approach. Synergistic effect between AZnMo-LDHs and VGCF reveals smaller electrical resistance. The AZnMo-LDHs@VGCF exhibited good sensing performance and recoveries to dimetridazole detection.